Microstructure Alterations of Ti-6Al-4V ELI during Turning by Using Tungsten Carbide Inserts under Dry Cutting Condition - Ibrahim G.A.; Arinal H.; . Zulhanif; Haron C.H.C. (University of Bandar Lampung (UBL), 2013)
Titanium alloys possesses a hexagonal close packed(h.c.p) structure, called phase to ambient temperature. Thisstructure changes to body center cubic (b.c.c), called phase tothe temperature of 882 C. Machining process that generates hightemperature during machining can affect on microstructures ofmachined surface, which represents as a quality of components.The turning parameters evaluated are cutting speed (55 - 95m/min), feed rate (0.15 - 0.35 mm/rev), depth of cut (0.10 - 0.20mm) and tool grade (uncoated, CVD and PVD). The aims of thispaper are to investigate the effects of machining process onmicrostructures of machined surface and chip were machinedusing tungsten carbide inserts under dry cutting condition. Theresults show that machining at high cutting speed (95 m/min)affected on the microstructure significantly at the end ofmachining. The temperature is the most significant factoraffected on microstructure of the machined surface and chip atshear zone. The changes of microstructure were also affected bythe tool pressure during cutting.